Space vehicle dynamics and control - Wie, Bong, 1952- (American Institute of Aeronautics and Astronautics, 1998)
Space Vehicle Dynamics and Control provides a solid foundation in dynamic modeling, analysis, and control of space vehicles. More than 200 figures, photographs, and tables are featured in detailed sections covering the fundamentals of controlling orbital, attitude, and structural motions of space vehicles. The textbook highlights a range of orbital maneuvering and control problems: orbital transfer, rendezvous, and halo orbit determination and control. Rotational maneuvering and attitude control problems of space vehicles under the influence of reaction jet firings, internal energy dissipation, or momentum transfer via reaction wheels and control moment gyros are treated in detail. The textbook also highlights the analysis and design of attitude control systems in the presence of structural flexibility and/or propellant sloshing. At the end of each chapter, Dr. Wie includes a helpful list of references for graduate students and working professionals studying spacecraft dynamics and control. A bibliography of more than 350 additional references in the field of spacecraft guidance, control, and dynamics is also provided at the end of the book. Space vehicle dynamics and control requires a thorough knowledge of vector and matrix algebra, calculus, ordinary differential equations, engineering mechanics, and linear system dynamics and control. The first two chapters provide a summary of such necessary background material. Since some problems may require the use of software for the analysis, control design, and numerical simulation, readers should have access to computational software (i.e., MATLAB) on a personal computer.
Keywords: Space vehicles -- Dynamics.; Space vehicles -- Control systems.; elektronické knihy; electronic books